Enlarging {110} exposed facets of anatase TiO2 by the synergistic action of capping agents. Issue 27 (2nd June 2016) - Li, Qiaoying; Li, Taoyun; Chang, Shunzhou; Tao, Qingsong; Tian, Baozhu; Zhang, Jinlong
Abstract : Anatase TiO2 microcrystals containing ∼15% highly reactive {110} facets were successfully synthesized by a one-step hydrothermal method, in which H2 O2, HF, and Cl − ions showed a synergistic effect on the formation of {110} facets. Abstract : Anatase TiO2 microcrystals containing ∼15% highly reactive {110} facets were successfully synthesized by a one-step hydrothermal method, in which H2 O2, HF, and Cl − ions showed a synergistic effect on the formation of {110} facets. Benefiting from the surface heterojunction structure, TiO2 microcrystals with {110} facets showed an enhanced photocatalytic activity for dye degradation.